2017
DOI: 10.1099/mic.0.000517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in galactooligosaccharide utilization in Bifidobacterium breve strain YIT 4014T

Abstract: Galactooligosaccharides (GOS) are mixed oligosaccharides that are mainly composed of galactosyllactoses (GLs), which include 3¢-GL, 4¢-GL, and 6¢-GL. Data from numerous in vitro and in vivo studies have shown that GOS selectively stimulate the growth of bifidobacteria. Previously, we identified the gene locus responsible for 4¢-GL utilization, but the selective routes of uptake and catabolism of 3¢-and 6¢-GL remain to be elucidated. In this study, we used differential transcriptomics to identify the utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In the formula-fed infant group (the USA only), the abundance of Bifidobacterium appeared to show strong positive correlations with those of GOS transporter genes with statistical significance [47,75] ( Figure 4B; Spearman's rank correlation coefficient). GOSs are world-wide prebiotics supplemented in infant formula and are known to increase the population of bifidobacteria in the guts [76,77].…”
Section: Abundance Of Hmo-related Genes Is Associated With Bifidobactmentioning
confidence: 99%
“…In the formula-fed infant group (the USA only), the abundance of Bifidobacterium appeared to show strong positive correlations with those of GOS transporter genes with statistical significance [47,75] ( Figure 4B; Spearman's rank correlation coefficient). GOSs are world-wide prebiotics supplemented in infant formula and are known to increase the population of bifidobacteria in the guts [76,77].…”
Section: Abundance Of Hmo-related Genes Is Associated With Bifidobactmentioning
confidence: 99%
“…Different ABC transporters appear to mediate this utilization, and the closest homolog of Bal6GBP (WP_003828494.1; amino acid sequence identity 76%) showed the highest affinity for ␤-(1,6)-GL (K D ϭ 0.357 M). This protein has a markedly different selectivity as compared with Bal6GBP, based on a decrease in affinity of only 16-fold for ␤-(1,4)-GL and 460-fold lower affinity for ␤-(1,3)-GL (22). The shared preference for ␤-(1,6)-galactosides, but large selectivity differences, are consistent with these SBPs populating different branches in the same clade in the phylogenetic tree (clade 1, Fig.…”
Section: The Selectivity Of Transport Binding Proteins Correlates To mentioning
confidence: 98%
“…lactis grows well on ␤-(1,6)galactosyl lactose, but not on the ␤-(1,4) version of this trisaccharide (both from bovine milk)) (36). Recent studies have identified an ABC transporter that mediates the uptake of ␤-(1,6)-galactosyl-lactose from B. breve and characterized the preference of the associated SBP (22,37). Notably, B. breve was EDITORS' PICK: ␤-Galactoside capture in B. animalis subsp.…”
Section: The Selectivity Of Transport Binding Proteins Correlates To mentioning
confidence: 99%
See 1 more Smart Citation
“…inulin, fructo‐oligosaccharides (FOS), galacto‐oligosaccharides (GOS), and lactulose . These saccharides selectively promote probiotic bacteria, as these bacteria often uniquely express special transporters to bind and uptake them and enzymes to utilize them . However, none of the existing prebiotic solutions for modulation of the gut microbiota contains a protein source.…”
Section: Introductionmentioning
confidence: 99%